Integrating green management case studies in construction engineering courses to improve students' critical thinking - Mingyi, Ying; Tang, Sai Hong; Supeni, Eris Elianddy; Yingqiao, Xia (Human Resources Management Academic Research Society (HRMARS), 2024)
With the growing need in the industry for sustainable practices and critical thinking abilities, the inclusion of green management case studies in construction engineering education is becoming more and more crucial. Developing these talents is frequently not possible with traditional educational approaches. This paper investigates the theoretical foundations and practical implementation of case-based learning in construction engineering courses, with a focus on green management, to show how it might enhance students' critical thinking abilities. The project intends to close the gap between academic learning and industrial expectations by incorporating real-world examples of eco-friendly materials, energy-efficient designs, and cutting-edge green technologies. The results emphasize the value of hands-on learning in helping students develop a deeper comprehension of sustainable practices and getting ready for the difficulties of contemporary construction engineering.